(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Postterm pregnancy is one of the pressing problems in obstetrics today, due to the high frequency of pathological processes on both the maternal and fetal sides. Postmaturity occurs in approximately 4-14% of cases. [2]. Despite the length of time that this problem has been studied, many issues related to post-term pregnancy remain incompletely studied and are still relevant today.